The Impact of a Swimming Training Season on Anthropometrics, Maturation, and Kinematics in 12-Year-Old and Under Age-Group Swimmers: A Network Analysis - Fiori, Júlia Mello; Bandeira, Paulo Felipe Ribeiro; Zacca, Rodrigo; Castro, Flávio Antônio de Souza (Frontiers in Sports and Active Living, 2022)
Multivariate models can provide new insights on changes in swimming performance beyond traditional statistical approaches. Through network analysis, we verified the relationships between anthropometrics, maturation, and kinematics changes () in 25-m breaststroke (BREAST) and butterfly (FLY) swimming performance, before and after a 47-week swimming training season. Twenty age-group swimmers (10.2 ± 1.2 y) performed a 25-m all-out swim test (T25) in BREAST and FLY techniques, before and after 47-weeks. Three measures of centrality, transformed into a z-score, were generated: betweenness, closeness and strength. Data was compared (t test) and effect sizes were identified with Hedges’ g. Large effect sizes were observed for swimming performance improvements in BREAST (32.0 ± 7.5 to 24.5 ± 3.8 s; g = 1.26;  = -21.9 %) and FLY (30.3 ± 7.0 to 21.8 ± 3.6 s; g = 1.52;  = -26.5 %). Small to moderate effect sizes were observed for anthropometric changes. Moderate effect size was observed for maturity offset changes (−2.0 ± 0.9 to −1.3 ± 1.0; g = 0.73;  = 50.9 ± 281 %). Changes in maturity offset, stroke rate, and stroke length for both BREAST and FLY swimming speeds were highlighted by the weight matrix. For betweenness, closeness, and strength changes in arm span (BREAST) and stroke length (FLY) were remarkable. The network strengthens the notion of complexity of changes in swimming performance, especially for simultaneous techniques in age-group swimmers.